KAJIAN KONSTITUSI TENTANG PERLINDUNGAN HAK ASASI MANUSIA TERHADAP ANAK JALANAN - Ambarsari, Ririen (JURNAL KONSTITUSI, 2011)
UNICEF provides restrictions Street children as "Children WHO work on the streets of urban areas, without reference to the time They Spend thereasons for being there or there". Various studies reveal the terrible situation faced by street children, as pursued by police, suffered torture, violence, utilized and exploited by the syndicates to become beggars, street musicians, pickpockets, and even some street children are also experiencing sexual exploitation. This phenomenon can be categorized as a form of violation of human rights that need protection. With regard to the legal protection of street children, weve set national laws, among others, in the 1945 Constitution, article 28 B, paragraph 2 which states that the rights of children to survival, grow and develop as well as the right to protection from violence and discrimination, the Law of Human Rights in 1999 where the protection of children provided for in article 52 to article 66, as well as the Law of the Republic of Indonesia Number 23 year 2002 on Child Protection.Â